A política externa chinesa na era de Xi Jinping - Lima, Anna Terra Costa Correia (2023)
This research focuses on contemporary Chinese foreign policy (FP), specifically Xi Jinping's foreign policy. Starting from the question: how does Chinese foreign policy thinking takes place in the era of Xi Jinping, and how does it materialize? This thesis seeks to understand and explore generally the characteristics of Xi Jinping’s government's foreign policy, and how it is conceived and implemented in practice. This research is based on the premise that there was a paradigm shift in the foreign policy of the new government, when the foreign policy stance governed by the principle “hide your strength, gain time” by Deng Xiaoping (1978-1992), that marked the period of reforms and economic development and lasted until Hu Jintao's government (2003-2013), was partially abandoned. For these purposes, a qualitative methodology will be used with a central focus on Foreign Policy Analysis, bringing two case studies. This work aims to result in a comprehensive and multilevel analysis of Chinese foreign policy, considering actors and structures.